2016
DOI: 10.1007/s12024-016-9828-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of road traffic accident casualties admitted to a tertiary care hospital in Sri Lanka

Abstract: The mortality and morbidity of road traffic accidents (RTA) is increasing in the South Asian region, including Sri Lanka. Therefore, the demographic factors, types of vehicles involved, and the severity of injuries sustained in RTA was studied. Age, gender, and details of the incident of all patients admitted to hospital following a RTA, between January 2007 and August 2012, were obtained by interview. Following a medico-legal examination, the type and severity of injuries was categorized as, non-grievous, gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 7 publications
4
14
0
1
Order By: Relevance
“…There is a male predominance in both groups on our study, but the injured female proportion is significantly higher among pillion riders (42%) compared to riders (10%). Several studies done in Sri Lanka, as well as global statistics, show the same vulnerability of males while being the commonest users [16] . It has been observed that the number of female drivers is drastically rising worldwide over the last couple of years with the introduction of userfriendly female conventional bicycles.…”
Section: Discussionmentioning
confidence: 89%
“…There is a male predominance in both groups on our study, but the injured female proportion is significantly higher among pillion riders (42%) compared to riders (10%). Several studies done in Sri Lanka, as well as global statistics, show the same vulnerability of males while being the commonest users [16] . It has been observed that the number of female drivers is drastically rising worldwide over the last couple of years with the introduction of userfriendly female conventional bicycles.…”
Section: Discussionmentioning
confidence: 89%
“…Injuries to the limbs which were the commonest in our study were similar to the injuries sustained by passengers of motorcycles. 13 However, this contrasted with the findings of Vadysinghe et al where the most affected region of the body was the head where they have described a similar mechanism of causation of injuries. 21 Three-wheelers are included in the term "traffic" defined in section 240 of the motor traffic act of Sri Lanka.…”
Section: Discussionmentioning
confidence: 58%
“…studies in the central province where the most vulnerable group was identified as 20-29 years among victims of all road traffic accidents and 21 -30 years in a study conducted on three-wheeler crashes. 5,13,14,15 The commonest type of incident seen was toppling of the vehicle. 5 However, a study done in the western province revealed that a majority of three-wheeler crashes were due to impact with another vehicle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations